DEVELOPMENT OF CONTEXTUAL-BASED MATHEMATICS STUDENT ACTIVITY SHEETS (LKS) AT SMP N 11 YOGYAKARTA - Fitrianingrum, Fitrianingrum (Nindikayla Institute, 2023)
The learning resources for grade 7 students of SMP N 11 Yogyakarta used are textbooks and worksheets containing a summary of the material. This study aims to create teaching materials in Mathematics LKS to facilitate student learning through contextual-based learning resources close to the student's environment. The test subjects in this study were 13 students of class 7B and 34 students of class 7A at SMP N 11 Yogyakarta. The LKS development method uses the ADDIE method, namelyanalysis, design. development, andimplementation. Data collection instruments using questionnaires and questionsposttest. The results of development research in the form of contextual-based math worksheets in the school environment are valid with a score of 72.86%, practical with a score of 4.02 from student responses and a percentage score of 92.31% implementation of learning, and effective with a score of 79%. So that LKS is suitable for use in learning mathematics on related material